2018
DOI: 10.1111/jocd.12817
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label, single‐site study to evaluate the tolerability, safety, and efficacy of using a novel facial moisturizer for preparation and accelerated healing pre and post a single full‐face radiofrequency microneedling treatment

Abstract: Summary Background Skincare cosmeceutical products have been shown to address intrinsic and extrinsic skin aging. Radiofrequency (RF) with microneedling is effective and safe in improving skin laxity and texture. Pairing skincare cosmeceutical products pre‐ and post‐procedure is beneficial as it enhances patient results, patient results, patient experience, and reduces patient downtime. Objective To evaluate the tolerability, safety, and efficacy of a multi‐ingredient anti‐aging facial moisturizer when applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…For example, because abrasion produces slight impairments of the skin barrier, 19 topical formulations used in conjunction with the procedure may reduce irritation and downtime. One previous study demonstrated the safety, tolerability and efficacy of a multi‐ingredient anti‐aging facial moisturizer, 20 when used pre‐ and postmicroneedling; while other investigators have shown that topical tri‐ and hexapeptide‐containing products hasten healing and complement aesthetic outcomes of microneedling 18 . Furthermore, by decreasing the severity and duration of the inflammatory period, the risks of causing a flare‐up of any pre‐existing inflammatory disease (eg, psoriasis, eczema, atopic, or contact dermatitis) may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because abrasion produces slight impairments of the skin barrier, 19 topical formulations used in conjunction with the procedure may reduce irritation and downtime. One previous study demonstrated the safety, tolerability and efficacy of a multi‐ingredient anti‐aging facial moisturizer, 20 when used pre‐ and postmicroneedling; while other investigators have shown that topical tri‐ and hexapeptide‐containing products hasten healing and complement aesthetic outcomes of microneedling 18 . Furthermore, by decreasing the severity and duration of the inflammatory period, the risks of causing a flare‐up of any pre‐existing inflammatory disease (eg, psoriasis, eczema, atopic, or contact dermatitis) may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The use of microneedling has demonstrated efficacy for treating dyschromia, atrophic scars, and for rejuvenating photodamaged skin on the face and décolleté . Although microneedling has an excellent safety profile, treatment‐related adverse events may include at least minor pain or discomfort, erythema, and edema . Based on the promising results of topical products containing tri‐ and hexapeptides formulated using proprietary TriHex Technology ® , the products used in the present study were developed to reduce the severity of treatment‐related adverse events and improving aesthetic outcomes following RF microneedling of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with an RFM device included 45 patients at three clinics in the United States. All of the patients experienced a 75% to 80% improvement in hyperhidrosis after three treatments with multiple passes with depths of 2.5 to 3.5 mm 10 …”
Section: Other Applications Of Rfmmentioning
confidence: 94%
“…Another study by the same group evaluated an antiaging multi‐ingredient lotion used twice daily for 2 weeks prior and 4 weeks post one RFM treatment in 15 patients. This regimen led to significant improvement in skin radiance, texture, tone, smoothness, redness, and overall appearance 10 . Another option is to apply platelet‐rich plasma after an RFM treatment.…”
Section: Introduction To Radiofrequency Microneedling (Rfm)mentioning
confidence: 99%